2018
DOI: 10.1016/j.socscimed.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Marital infidelity, food insecurity, and couple instability: A web of challenges for dyadic coordination around antiretroviral therapy

Abstract: Couples-based interventions targeting ART adherence should improve relationship quality, while also addressing interpersonal stressors such as marital infidelity and food insecurity. Multi-level interventions that address both dyadic and structural levels may be necessary for couples with severe food insecurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…There was a statistically signi cant association between depression and spousal extra marital affairs among our study participants which echoes ndings of previous studies done in LMICs [13,14,43]. Many men involved in extramarital relationships show inadequate love, offer no emotional support and care to their wives which increases the risk of separation and divorce, stress, and anxiety among couples [13,44]. Culturally, divorce is not common in Uganda setting with only 7% of the population getting divorce [45].…”
Section: Discussionsupporting
confidence: 79%
“…There was a statistically signi cant association between depression and spousal extra marital affairs among our study participants which echoes ndings of previous studies done in LMICs [13,14,43]. Many men involved in extramarital relationships show inadequate love, offer no emotional support and care to their wives which increases the risk of separation and divorce, stress, and anxiety among couples [13,44]. Culturally, divorce is not common in Uganda setting with only 7% of the population getting divorce [45].…”
Section: Discussionsupporting
confidence: 79%
“…Couple-based interventions for HIV prevention have demonstrated that strengthening interpersonal communication can lead to increased HIV testing and reduced sexual risk behavior [ 33 35 ]. These findings, along with a growing body of research, [ 13 , 23 , 24 , 33 42 ] demonstrate the importance of dyadic-level influence on HIV prevention and treatment.…”
Section: Introductionmentioning
confidence: 73%
“…Follow-up interviews with participants found that decisions were strongly influenced by perceived support or disapproval from partners, families, and communities [ 21 , 22 ]. Research among heterosexual couples in sub-Saharan Africa have found several distinct patterns of partner influence on ART adherence—both positive (e.g., providing support) and negative (e.g., control and conflict)—that are informed by relationship quality, power dynamics, and structural factors [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 , 12 , 46 Usually, men involving in extramarital relationships show inadequate love and offer no emotional support and care to their wives, which increases the risk of separation and divorce, and ultimately turns mental instabilities among couples. 12 , 47 Culturally, divorce is not common in Uganda, with only 7% of the population getting a divorce. 48 As such, most women choose to stay in these relationships with increased exposure to stress and hence depression.…”
Section: Discussionmentioning
confidence: 99%